Wybrane rodzinne uwarunkowania tożsamości społeczno-kulturowej studentów w wymiarze religijnym - Sobecki , Mirosław (Kultura-Społeczeństwo-Edukacja, 2021)
The article contains selected results of research from spring 2020 among students of universities in Białystok. The author distinguished 9 types of socio-cultural identity in the religious dimension. He also made an attempt to establish a relationship between these types and selected features of the family environment. The following were used as independent variables: the level of parents’ education, opinions of the surveyed students on the level of parents’ religiosity and the relationship between the respondents and their parents in childhood and adolescence. The relationship between the number of children in the respondent’s family and the type of social and cultural identity in the religious dimension were also analyzed.